Sifat Kimia dan Palatabilitas Nugget Ayam Menggunakan Jenis dan Konsentrasi Bahan Pengisi yang Berbeda - Iis Yuanita; Lisnawaty Silitonga (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
The purpose of this study is to know the influence of type and concentration of substance of chicken nugget to chemical content and nugget palatability. This research was done by using three types of substance. Those are maizena, tapioca and wheat; three concentrations, those are 0%, 1.5%, 2.5%. The result of this research was the chemical nugget product quality with different types and concentration has variation. The highest water content was found in nugget with 2.5 % tapioca, and the lowest was in nugget maizena 2.5%. Meanwhile, the highest ash content was in nugget maizena 1.5% and the lowest was in nugget without any substance (0%). The highest protein content was in nugget without any susbstance (0%) and the lowest was in wheat nugget 2.5%. For each highest and lowest fat contents was on maizena 1.5% and wheat nugget 2.5%, while the highest carbohydrate content was in maizena 1.5% and the lowest was in nugget without any substance (0%). Preference test showed that nuggets with maizena, tapioca and wheat as substances on different concentration relatively were liked and acceptable, all product color, texture, solidness, smell and taste. It was concluded that nugget with 1.5% maizena as substance has the best chemical quality among the treatments.